Per cent emphysema is associated with respiratory and lung cancer mortality in the general population: a cohort study. Issue 7 (5th April 2016) - Oelsner, Elizabeth C; Carr, J Jeffrey; Enright, Paul L; Hoffman, Eric A; Folsom, Aaron R; Kawut, Steven M; Kronmal, Richard A; Lederer, David J; Lima, Joao A C; Lovasi, Gina S; Smith, Benjamin M; Shea, Steven J; et al.
Abstract : Background: Emphysema on CT is a risk factor for all-cause mortality in persons with and without airflow obstruction; however, causes of death associated with emphysema remain uncertain, particularly in the general population. Aims: To test associations between quantitatively assessed emphysema on CT and cause of death in persons with and without a substantial smoking history. Methods: The Multi-Ethnic Study of Atherosclerosis recruited 6814 participants, aged 45–84 years and without clinical cardiovascular disease, in 2000–2002. Per cent emphysema was defined on cardiac CT as per cent of lung voxels less than −950 Hounsfield units; emphysema on CT was defined as per cent emphysema above the upper limit of normal. Cause of death was classified by administrative codes. Proportional-hazards models were adjusted for age, race/ethnicity, gender, body mass index, smoking status, pack-years, coronary artery calcium, site and education. Additional adjustment for lung function was made in a subset with spirometry from 2004 to 2006. Results: There were 1091 deaths over 12 years median follow-up. Emphysema on CT was strongly associated with increased mortality due to respiratory diseases (adjusted HR 2.94, 95% CI 1.68 to 5.15), particularly chronic lower respiratory diseases (adjusted HR 9.54, 95% CI 4.70 to 19.35), and lung cancer (adjusted HR 1.84, 95% CI 1.09 to 3.12), but not cardiovascular disease. Associations persisted among participants with fewer than 10 pack-years and those without physician-diagnosed respiratory disease, and were similar after adjustment for airflow measures and in persons without airflow limitation. Conclusions: Quantitatively assessed emphysema on CT is associated with greater respiratory disease and lung cancer mortality, even among persons without traditional risk factors.